Ultra-fast charge migration competes with proton transfer in the early chemistry of H2O˙+. Issue 4 (12th January 2017) - Wang, Furong; Schmidhammer, Uli; de La Lande, Aurélien; Mostafavi, Mehran
Abstract : Oxidation by the ultra-short lived radical cation of water, H2 O˙ +, can potentially take place at the interface of water and numerous heterogeneous systems involved in radiation therapy, energy and environmental industries. Abstract : Oxidation by the ultra-short lived radical cation of water, H2 O˙ +, can potentially take place at the interface of water and numerous heterogeneous systems involved in radiation therapy, energy and environmental industries. The oxidation processes induced by H2 O˙ + can be mimicked in highly concentrated solutions where the nearest neighbors of H2 O˙ + may be molecules other than water. The reactivity of H2 O˙ + and D2 O˙ + is probed in hydrogenated and deuterated sulfuric acid solutions of various concentrations. The oxidized solute, sulfate radical, is observed at 7 ps and remarkably higher yields are found in deuterated solutions. The isotopic effects reveal the competition between two ultrafast reactions: proton transfer toward H2 O (D2 O) and electron transfer from HSO4 − to H2 O˙ + (D2 O˙ + ). Density functional theory simulations decipher the electron transfer mechanism: it proceeds via sub-femtosecond charge migration and is not affected by isotopic substitution. This work definitively demonstrates why direct oxidation triggered by H2 O˙ + can be competitive with proton transfer.